Prevalence of Anemia among Adolescent Schools Girls of Delhi: A Cross Sectional School Based Study - Monika Singh; Om Prakash Rajoura; Raghavendra A Honnakamble (National Journal of Community Medicine, 2019)
Background: Anemia is one of the major public health problems in women of developing countries. Recent studies in India have shown that around 90% of adolescent girls are anemic.